Carolina cradle : settlement of the northwest Carolina frontier, 1747-1762 - Ramsey, Robert Wayne (University of North Carolina Press, 1987)
Describes the "invasion" of emigrant families into the area and their socio-economic and religious reasons for migrating during the period. A #87-442 Gift-Friends of the Genealogy Collection